Clinical Outcomes in 3343 Children and Adults With Rheumatic Heart Disease From 14 Low- and Middle-Income Countries: Two-Year Follow-Up of the Global Rheumatic Heart Disease Registry (the REMEDY Study). Issue 19 (8th November 2016) - Zühlke, Liesl; Karthikeyan, Ganesan; Engel, Mark E.; Rangarajan, Sumathy; Mackie, Pam; Cupido-Katya Mauff, Blanche; Islam, Shofiqul; Daniels, Rezeen; Francis, Veronica; Ogendo, Stephen; Gitura, Bernard; Mondo, Charles; et al.
Abstract : Background: There are few contemporary data on the mortality and morbidity associated with rheumatic heart disease or information on their predictors. We report the 2-year follow-up of individuals with rheumatic heart disease from 14 low- and middle-income countries in Africa and Asia. Methods: Between January 2010 and November 2012, we enrolled 3343 patients from 25 centers in 14 countries and followed them for 2 years to assess mortality, congestive heart failure, stroke or transient ischemic attack, recurrent acute rheumatic fever, and infective endocarditis. Results: Vital status at 24 months was known for 2960 (88.5%) patients. Two-thirds were female. Although patients were young (median age, 28 years; interquartile range, 18–40), the 2-year case fatality rate was high (500 deaths, 16.9%). Mortality rate was 116.3/1000 patient-years in the first year and 65.4/1000 patient-years in the second year. Median age at death was 28.7 years. Independent predictors of death were severe valve disease (hazard ratio [HR], 2.36; 95% confidence interval [CI], 1.80–3.11), congestive heart failure (HR, 2.16; 95% CI, 1.70–2.72), New York Heart Association functional class III/IV (HR, 1.67; 95% CI, 1.32–2.10), atrial fibrillation (HR, 1.40; 95% CI, 1.10–1.78), and older age (HR, 1.02; 95% CI, 1.01–1.02 per year increase) at enrollment. Postprimary education (HR, 0.67; 95% CI, 0.54–0.85) and female sex (HR, 0.65; 95% CI, 0.52–0.80) were associated with lower risk of death. Two hundred and four (6.9%) patients had new congestive heart failure (incidence, 38.42/1000 patient-years), 46 (1.6%) had a stroke or transient ischemic attack (8.45/1000 patient-years), 19 (0.6%) had recurrent acute rheumatic fever (3.49/1000 patient-years), and 20 (0.7%) had infective endocarditis (3.65/1000 patient-years). Previous stroke and older age were independent predictors of stroke/transient ischemic attack or systemic embolism. Patients from low- and lower-middle–income countries had significantly higher age- and sex-adjusted mortality than patients from upper-middle–income countries. Valve surgery was significantly more common in upper-middle–income than in lower-middle– or low-income countries. Conclusions: Patients with clinical rheumatic heart disease have high mortality and morbidity despite being young; those from low- and lower-middle–income countries had a poorer prognosis associated with advanced disease and low education. Programs focused on early detection and the treatment of clinical rheumatic heart disease are required to improve outcomes. Abstract : Supplemental Digital Content is available in the text.